Pengembangan Sistem Informasi Geografi Untuk Pemantauan Jaringan Irigasi Menggunakan LeafletJS - Sumarsono Sumarsono; Choerun Asnawi; Evy Kusumaningrum; Dedy Hariyadi (Lembaga Penelitian, Pengabdian Kepada Masyarakat dan Publikasi (LPPMP), 2023)
The distribution or flow of water in irrigation networks that are not good can have an impact on air demand on agricultural land. This is due to the air volume that is not optimal due to damage to the irrigation network. Each irrigation network has a level of disturbance which is measured by the level of damage to the irrigation network based on the channel and building arrangement. Efforts to anticipate the level of damage to the wider irrigation network that can harm farmers, it is necessary to have a system that makes it easier for air interpreters to provide reports. Based on the report, the water interpreter will be followed up and processed by the team regarding more handling. In the ease of reporting, water interpreters need a location-based reporting system. Therefore, the right approach in reporting damage to irrigation networks is using a geographic information system. With the development of internet communication, geographic information systems have been developed that can be implemented on smartphones with the Android operating system.